ASSESSMENT OF HEALTH CENTERS AND HOSPITALS ABOUT THE EFFECTIVENESS OF MATERNAL REFERRAL SYSTEM IN SURABAYA DISTRICT - Yonara, Stevie; Wulandari, Ratna Dwi (Universitas Airlangga, 2015)
ABSTRACT More than 80.0% maternal deaths occured in hospital in Surabaya between 2012-2014. Most of them who died in hospital were referral patients from midwife, private clinics, and public health centers. This study assessed the effectiveness of maternal referral system based on perspective of public health centers and hospitals in Surabaya. This was a descriptive cross sectional study. Samples were 43 public health centers in Surabaya and two main referral destination hospitals. Data was collected by interviewing one representative midwife in each public health center and hospital. This study showed that a total of 81.4% health centers assess that maternal referral system in Surabaya District was quite effective. While, one of the hospital assessed quite effective, and the other assessed less effective. The reason was because public health centers difficulty to contacting hospitals about referral, hospitals often rejected referral case, pregnant women often do self-referral to hospital, and incompatibility referral reason by most of public health centers. So it was necessary to repair maternal referral system at Surabaya based on identification of each variables in effectiveness of maternal referral system.Keywords: effectiveness, hospitals, maternal refferal system, public health center